A 12,000 year record of changes in herbivore niche separation and palaeoclimate (Wonderwerk Cave, South Africa) - Ecker, M; Brink, J; Horwitz, L; Scott, L; Lee-Thorp, J (Elsevier, 2017)
The large mammalian fauna of southern Africa today is characterised by strong niche separation into grazer and browser species, with few falling into the intermediate mixed-feeder niche. Moreover, the modern fauna is reduced in species diversity compared to the Pleistocene, following the extinction of several specialized grazers in the late Pleistocene and early Holocene. How did this state develop, and how might it be connected to climatic change during the Holocene? To better understand this development, we obtained extensive carbon and oxygen stable light isotope data from herbivore tooth enamel samples from Wonderwerk Cave, South Africa, spanning about 12,000 to 500 cal. BP. This is a unique dataset since it is the only site in the southern Kalahari with a robust chronometric record and well-preserved faunal remains for the last 12,000 years without significant gaps. Combining the stable isotopes with pollen and micromammal data from Wonderwerk Cave, we have explored shifts in the proportions of C3 and C4 plants and moisture availability. Although climate remained generally semi-arid for much of this period, the results show significant hydrological and vegetation shifts in the sequence, particularly with the strengthening of summer rainfall in the mid-Holocene. The results for the sixteen herbivore species reveal a reinforcement of the grazer-browser niche partitioning through the Holocene and shows how niche specialization follows changes in local vegetation composition. In the light of this reconstruction of the local ecology we discuss grazer extinctions, human adaptations, and the drivers behind climatic changes in the summer rainfall zone of southern Africa.